Taxonomic revision of the longicorn beetle genus Uracanthus Hope 1833 (Coleoptera: Cerambycidae: Cerambycinae: Uracanthini) from Australia - Thongphak, Duangrat; Wang, Qiao (Zootaxa, 2007)
A thorough taxonomic revision of the Australian Uracanthus is provided, including a redefinition of the scope of the genus, descriptions and illustrations of new and previously known species, and a key to all species. The revised Australian Uracanthus includes 39 species, eight of which are established as new to science: U. pseudogigas sp. nov., U. maculatus sp. nov., U. griseus sp. nov., U. bicoloratus sp. nov., U. perthensis sp. nov., U. punctulatus sp. nov., U. quadristriolatus sp. nov., and U. bistriolatus sp. nov. Six new synonyms are proposed (senior synonyms last): U. multilineatus McKeown with U. ventralis Lea, U. dentiapicalis McKeown with U. parvus Lea, U. marginellus Hope and U. inermis Lea (not Aurivillius) with U. bivitta Newman, U. fuscostriatus McKeown with U. lateroalbus Lea, and U. daviumbus Gressitt with U. longicornis Lea. Dorsal views of all species are presented as photographs, terminalia of both sexes illustrated, and distributions mapped. The larvae of this genus are borers of at least 31 genera of trees and parasitic plants in 15 families (Asteraceae, Betulaceae, Casuarinaceae, Cupressaceae, Fabaceae, Loranthaceae, Myrtaceae, Pittosporaceae, Proteaceae, Rhamnaceae, Rosaceae, Rutaceae, Sapindaceae, Sterculiaceae, and Xanthorrhoeaceae), including some economically important crops such as citrus, lychee (or litchi), peach, plum, and apricot. Several species are important pests of orchards. Uracanthus adults visit flowers of various tree species and are attracted to the light.